Pearl Jephcott: girls' club worker. Issue 5 (29th July 2019) - Jeffs, Tony
ABSTRACT: Pearl Jephcott (1900–1980) between 1922 and 1946 was by turns a volunteer girls' club worker, Organising Secretary for the Birmingham Union of Girls' Clubs, the occupant of a similar post in County Durham and finally the Publications Officer for the National Association of Girls' Clubs. During most of that period she combined girls' club work with helping to pioneer new forms of practitioner research. The article examines her contribution to both these fields during this period.